EVALUATION OF NEAR-INFRARED SPECTROSCOPY MONITORING IN SELECTIVE SHUNTING DURING CAROTID ENDARTERECTOMY - Gramatnikovski, N; Kondov B; Kokareva A; Simeonova A; Josifov A; Jovanovski-Srceva M (Department of Anaesthesia and Reanimation, Faculty of Medicine, Ss. Cyril and Methodius University, Skopje, R.N. Macedonia, 2020)
Background: Carotid endarterectomy (CEA) is a standard prophylactic treatment of symptomatic and asymptomatic carotid stenosis. CEA can be performed either by conventional or eversion techniques. No matter what technique is used, cross-clamping of the carotid artery increases the risks for cerebral ischemia and hypoperfusion. Carotid artery shunting used as an alternative method to prevent cerebral hypoperfusion by many clinicians, is not proven as reli- able procedure that exposes patients to additional risks. However, literature supports findings of monitoring and vigilance methods that can be used as predictors when shunting is required. The aim of our study was to evaluate near infrared spectroscopy (NIRS) as a noninvasive method for the monitoring of regional cerebral oxygenation (rSO2) during carotid cross-clamping and its reliability for the requirement of shunting in patients undergoing CEA.
Keywords: carotid endarterectomy; local anesthesia; near-infrared spectroscopy